Performance and Serum Hepatic Enzymes of Hy-Line W-36 Laying Hens Intoxicated with Dietary Carbon Tetrachloride - Hadavi A; Kermanshahi H; Nassiri Moghaddam H; Golian A (Poultry Science Journal, 2015)
An experiment was conducted to study the effects of carbon tetrachloride (CCl4) on post-peak performance and serum enzymes of Hy-Line W-36 laying hens from 32-36 weeks of age. The experiment was carried out with a total of 192 laying hens in a completely randomized block design. During the experiment laying hens were allocated to 4 groups consisted of T1) no CCl4 as control diet, T2, T3 and T4) control diet supplemented with 1, 3 and 5 mL CCl4/100 g diet, respectively. Each experimental group was divided into 6 blocks of 8 hens each. Egg production, cracked egg percentage and feed intake were recorded weekly. Blood samples were taken from wing veins of hens at the middle and end of the experiment to measure serum hepatic enzymes of alkaline phosphatase, alanine aminotransferase and aspartate aminotransferase. Data showed that in comparison with the control group, the inclusion of CCl4 to the diets had no significant effect on performance parameters. However, by increasing the level of CCl4, egg production was linearly decreased and feed intake was linearly increased (P < 0.05). The effect of CCl4 on cracked eggs was significant and this effect was linearly increased (P < 0.05). Dietary supplementation of 3 and 5 mL CCl4 elevated the serum concentration of hepatic enzymes of alkaline phosphatase, aspartate aminotransferase and alanine aminotransferase, linearly (P < 0.0001). In conclusion, the dietary supplementation of CCl4 has the ability to decrease the performance and egg quality. CCl4 is also a potent hepatic toxicity inducer and may damage liver hepatocytes. Therefore, the level of 3 mL CCl4 was assigned as the one had the maximum negative effect on serum hepatic enzymes concentration (maximum liver damage) alongside the minimum negative effect on laying hen performance for further studies.